Transport and transit potential of Uzbekistan and the role of Surkhandarya region (Zien Journal of Social Sciences and Humanities, 2023)
This article focuses on the transit potential of Uzbekistan, including the role of the Surkhandarya region, the influence of the region's geographical location on the transport-transit system, ways to increase the efficiency of transit opportunities, and the transit status of the region's transport networks.